2015
DOI: 10.1111/apt.13159
|View full text |Cite
|
Sign up to set email alerts
|

New onset idiosyncratic liver enzyme elevations with biological therapy in inflammatory bowel disease

Abstract: SUMMARY BackgroundAnti-tumour necrosis factor a (anti-TNF) agents have been implicated in drug-induced liver injury. There is minimal data on this occurrence in inflammatory bowel disease (IBD) patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
60
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 32 publications
4
60
0
3
Order By: Relevance
“…Overall, 48 cases were considered due to anti-TNF-α medications. The majority displayed autoimmune characteristics with positive serological markers [94]. …”
Section: Anti-tnf-α Liver Toxicitymentioning
confidence: 99%
“…Overall, 48 cases were considered due to anti-TNF-α medications. The majority displayed autoimmune characteristics with positive serological markers [94]. …”
Section: Anti-tnf-α Liver Toxicitymentioning
confidence: 99%
“…As the indications for the anti-TNF-α class of medications expanded and usage became more widespread, case series were collected, further providing evidence that there was an association between TNF-α antagonists and liver injury [26]. Over the past few years, several larger studies—including queries of large databases of patients on anti-TNF-α therapy and liver injury networks—have been published, and these have helped to better characterize the liver injury patterns that are encountered [8, 2729]. …”
Section: Reported Adverse Effects: Focus On Dilimentioning
confidence: 99%
“…In the majority (8/11) of the cases, the authors felt it was highly probable that the liver injury was due to the anti-TNF-α medications [27]. Similarly, a recent paper by Shelton et al [29] reported a retrospective cohort review of patients from two large academic medical centres and their affiliated clinics. These authors found 102 cases of elevated serum alanine aminotransferase levels in patients with inflammatory bowel disease on anti-TNF-α therapy, of which 48 were felt to be due to anti-TNF-α therapy, based on RUCAM analysis (Table 2) [29].…”
Section: Reported Adverse Effects: Focus On Dilimentioning
confidence: 99%
See 2 more Smart Citations